Antibacterial Activity and Optimisation of Bacteriocin Producing Lactic Acid Bacteria Isolated from Beef (Red Meat) Samples: Bacteriocin Producing Bacteria from Beef Samples (Biological Sciences - PJSIR, 2016)
Bacteriocin producing bacteria are commonly found in meat products to enhance theirshelf-life. In the present study, bacterial species were isolated from meat samples (beef) from differentlocalities of Lahore, Pakistan. MRS agar medium was used to isolate lactic acid bacteria (LAB) throughspread and streak methods (incubated for 72 h at 37 °C). Identification of bacteriocinogenic LAB strainswas done by using staining techniques, morphology based characteristics and biochemical tests. Thesestrains were BSH 1b, BSH 3a, BIP 4a, BIP 3a, BIP 1b and BRR 3a. Antibacterial activity of LAB wasperformed against food borne pathogens viz., Escherichia coli and Staphylococcus aureus through paperdisc diffusion method. Three bacterial strains showed maximum inhibition and characterised by ribotypingviz., BIP 4a was identified as Lactobacillus curvatus, BIP 3a was Staphylococcus warneri and BIP 1b wasLactobacillus graminis. Optimum pH 5-6.5 and 30-37 °C temperature for isolated bacterial strains wasrecorded. Protein concentration measured was 0.07 mg/mL for BSH 1b, 0.065 mg/mL for BSH 3a,0.057 mg/mL for BIP 4a, 0.062 mg/mL for BIP 1b, 0.065 mg/mL for BIP 3a and for BRR 3a 0.078 mg/mL,respectively. Bacteriocin of all isolates except BIP 3a was found to be sensitive towards pepsin and resistanttowards Rnase. Bacteriocin production was stable at between pH 5.0 and 6.0 and resistant temperaturewas 40 °C. It was concluded that lactic acid bacteria (LAB) from meat can be helpful as antibacterialagents against food-borne bacterial pathogens because of thermostable producing bacteriocin.